Norway and black rats in Europe: potential reservoirs for zoonotic arthropod‐borne pathogens?. Issue 6 (28th February 2019) - Obiegala, Anna; Heuser, Elisa; Ryll, René; Imholt, Christian; Fürst, Johanna; Prautsch, Lisa‐Marie; Plenge‐Bönig, Anita; Ulrich, Rainer G; Pfeffer, Martin
ABSTRACT: BACKGROUND: Norway rats ( Rattus norvegicus ) and black rats ( R. rattus ) are known to be cosmopolitan reservoirs for zoonotic agents. Nevertheless, little is known about prevalence and distribution of arthropod‐borne pathogens in rats from Europe. Therefore, this survey focused on the detection of arthropod‐borne pathogens. Spleen‐derived DNA samples were available from 528 Norway rats and 74 black rats collected in several European countries. Further, these samples were processed by polymerase chain reaction for the detection of zoonotic pathogens such as Anaplasma phagocytophilum, Candidatus Neoehrlichia mikurensis (CNM), Babesia spp. and Bartonella spp. eventually followed by sequencing. RESULTS: Babesia spp. was not detected. Four Norway rat samples were positive for A. phagocytophilum DNA and two for CNM. In 50 rat samples, Bartonella spp. DNA was detected (8.1%; 95% Confidence interval (CI) 6.2–10.61). Whereas B. tribocorum ( n = 45) and B. grahamii ( n = 1) were carried exclusively in Norway rats from Central Europe (Belgium, Germany), B. coopersplainsensis ( n = 4) was detected only in black rats from southern European countries (Spain, Italy). CONCLUSIONS: Pathogenic Bartonella spp. DNA was found in black and Norway rats from Germany, Italy, Spain and Belgium for the first time. Bartonellae were found focally in zoos suggesting Norway rats as a possible reservoir for B. tribocorum and black rats as a reservoir for B. coopersplainsensis in Europe. These findings should raise awareness of pathogenic Bartonella spp. in Norway rats, especially in terms of pest management control in zoos. Norway and black rats seem not to be predominantly involved in the life cycle of the other examined arthropod‐borne pathogens in Europe. © 2019 Society of Chemical Industry Abstract : Bartonellae were found in rats from Germany, Italy, Spain and Belgium for the first time, suggesting Norway rats as possible reservoirs for B. tribocorum and black rats as possible reservoirs for B. coopersplainsensis .